PENGARUH STRATEGI PEMASARAN DIGITAL DAN HARGA TERHADAP VOLUME PENJUALAN PRODUK HNI-HPAI DI AGEN HALAL MART AGENCY CENTER ASIH MTQ MUARA BULIAN - Evi Kholishoh Ainuz Zulva; Sukatin Sukatin; Raden Hebat Kurnia; Dini Haryati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of digital marketing strategies and prices on sales volume at the Halal Mart Agency Center Asih Agent. This study uses a quantitative method. to research a certain population or sample. The population in this sample is the number of consumers who purchase HNI HPAL products in 2023. The data collection techniques used by researchers are observation, interviews and questionnaires. The analysis technique used is multiple linear regression to measure the effect of independent variables (digital marketing strategies and prices) on the dependent variable (sales volume). The results of this study indicate that there is a significant influence between digital marketing strategies on sales volume, there is a significant influence between prices on sales volume and there is a significant influence between digital marketing strategies and prices on sales volume